Antibacterial and Anti-Glucosyltransferase Activity of Verbascum speciosum Against Cariogenic Streptococci - Shabnam Pourmoslemi; Amir Larki-Harchegani; Sajad Daneshyar; Dara Dastan; Amir Nili-Ahmadabadi; Mina Jazaeri (Korean Pharmacopuncture Institute, 2023)
Objectives: Dental caries is a prevalent chronic human infection worldwide and several plants have shown anticariogenic properties through antibacterial activity against oral pathogens. The present study aimed to assess anticariogenic activity of Verbascum speciosum, in search of novel agents for the prevention and treatment of dental caries.Methods: Hydro-alcoholic extracts from flowers and total aerial parts of the plant were prepared by maceration. Antibacterial activity of the extracts against Streptococcus mutans (ATCC 35668) and Streptococcus sobrinus (ATCC 27607) was investigated by agar diffusion and microdilution techniques. Inhibitory concentration-fifty values of the flowers' extract against Streptococcus mutans glucosyltransferase enzymes were determined. The total flavonoid content of the extracts was determined using an aluminum chloride reaction.Results: Verbascum speciosum flowers' extract showed significantly higher flavonoid content and antibacterial activity; with minimum inhibitory concentrations of 100 and 200 μg/mL for Streptococcus mutans and Streptococcus sobrinus , respectively. The extract inhibited the synthesis of glucan by cell-associated and extracellular glucosyltransferase enzymes in a dose-dependent manner with higher activity against the extracellular enzyme.Conclusion: This study indicated effective anticariogenic activity of Verbascum speciosum flowers extract. This extract can be considered as an alternative to current anticaries therapies or an additive to dental care products.